Enhanced up-conversion and temperature-sensing behaviour of Er3+ and Yb3+ co-doped Y2Ti2O7 by incorporation of Li+ ions - Singh B.P.; Parchur A.K.; Ningthoujam R.S.; Ramakrishna P.V.; Singh S.; Singh P.; Rai S.B.; Maalej R. (My University, 2025)
Y2Ti2O7: Er3+/Yb3+ (EYYTO) phosphors co-doped with Li+ ions were synthesized by a conventional solid-state ceramic method. X-ray diffraction studies show that all the Li+ co-doped EYYTO samples are highly crystalline in nature with pyrochlore face centred cubic structure. X-ray photon spectroscopy studies reveal that the incorporation of Li+ ions creates the defects and/or vacancies associated with the sample surface. The effect of Li+ ions on the photoluminescence up-conversion intensity of EYYTO was studied in detail. The up-conversion study under ∼976 nm excitation for different concentrations of Li+ ions showed that the green and red band intensities were significantly enhanced. The 2 at% Li+ ion co-doped EYYTO samples showed nearly 15- and 8-fold enhancements in green and red band up-converted intensities compared to Li+ ion free EYYTO. The process involved in the up-conversion emission was evaluated in detail by pump power dependence, the energy level diagram, and decay analysis. The incorporation of Li+ ions modified the crystal field around the Er3+ ions, thus improving the up-conversion intensity. To investigate the sensing application of the synthesized phosphor materials, temperature-sensing performance was evaluated using the fluorescence intensity ratio technique. Appreciable temperature sensitivity was obtained using the synthesized phosphor material, indicating its applicability as a high-temperature-sensing probe. The maximum sensitivity was found to be 0.0067 K-1 at 363 K. © the Partner Organisations 2014.